Denudation - Sediment Accumulation Systems: Quantitative Aspects of Terrestrial Sediment Yield and Basin Filling - Gerhard Einsele (Ikatan Ahli Geologi Indonesia, 1998)
The role of terrestrial sediment supply in basin filling and sequence stratigraphy has been frequently mentioned, but quantitative data have been rarely presented and evaluated.